Real Lithuanian economic growth forecasting using artificial neural networks - Audronė Jakaitienė; Minija Tamošiūnaitė (Lietuvos Matematikos Rinkinys)
Methods for forecasting of Lithuanian gross domestic product (GDP) are analyzed. Prognoses obtained by means of linear models and artificial neural networks are compared.